Education Crisis in Nigeria Challenges of Reality and Future Prospects - Mahmoud, Roqaya Mohammad; Al-Anbaky, Taha Hameed Hasan (International Journal of Psychosocial Rehabilitation, 2020)
The education crisis is one of the most serious crises that Nigeria has faced since its independence, due to the fact that the progress of nations and peoples is dependent on development in the field of education, and accordingly that crisis had a profound effect on the deterioration of the social, economic and political conditions, which contributed to the continuing phenomenon of instability in the country, despite many programs and plans developed by successive governments to stop the deterioration in the education sector and work to develop it.